PERBAIKAN SANITASI DAN HYGIENE PRODUK BANDENG PRESTO AR PUTRA MAJU JAYA DI DESA TEGAL ARUM, MOJOSONGO, SURAKARTA - Raden Baskara Katri Anandito; Siswanti Siswanti; Lukita Purnamayati; Bara Yudhistira (Universitas Sebelas Maret, 2019)
Tegal Arum Village is one of the presto milkfish processing areas in Surakarta. One of the household industries that has been running for a long time with this business is Mr. Darpo's milkfish presto owned by the name IRT